Effect of Target Power on Microstructure, Tribological Performance and Biocompatibility of Magnetron Sputtered Amorphous Carbon Coatings - Dhandapani, Vishnu Shankar; Subbiah, Ramesh; Thangavel, Elangovan; Kim, Chang-Lae; Kang, Kyoung-Mo; Veeraraghavan, Veeravazhuthi; Park, Kwideok; Kim, Dae-Eun; Park, Dongkyou; Kim, Byungki (MDPI Open Access Publishing, 2023)
The tribological properties and preosteoblast behavior of an RF magnetron-sputtered amorphous carbon coating on a Si (100) substrate were evaluated. The graphite target power was varied from 200 to 500 W to obtain various coating structures. The amorphous nature of the coatings was confirmed via Raman analysis. The contact angle also increased from 58o to 103o, which confirmed the transformation of the a-C surface from a hydrophilic to hydrophobic nature with an increasing graphite target power. A minimum wear rate of about 4.73 x 10-8 mm3/N*mm was obtained for an a-C coating deposited at a 300 W target power. The 300 W and 400 W target power coatings possessed good tribological properties, and the 500 W coating possessed better cell viability and adhesion on the substrate. The results suggest that the microstructure, wettability, tribological behavior and biocompatibility of the a-C coating were highly dependent on the target power of the graphite. A Finite Element Analysis (FEA) showed a considerable increase in the Von Mises stress as the mesh size decreased. Considering both the cell viability and tribological properties, the 400 W target power coating was identified to have the best tribological property as well as biocompatibility.